The association between sarcoidosis and lymphoma: a retrospective and multicentre study of 46 patients. - Charriere, Romé; El Jammal, Thomas; Bert, Arthur; Chalayer, Emilie; Kilian, Martin; Gerfaud-Valentin, Mathieu; Jamilloux, Yvan; Ghesquieres, Hervé; Seve, Pascal (Sarcoidosis, Vasculitis and Diffuse Lung Diseases, 2025)
Background: Studies on sarcoidosis-lymphoma syndrome are scarce, and the association between these diseases is poorly understood. Aim: To analyse the features of three types of sarcoidosis-lymphoma association (SLA) according to the time of diagnosis of both diseases and to compare the features of patients who presented with sarcoidosis before lymphoma with those of patients with sarcoidosis alone (SA) in order to identify predictive factors of lymphoma development. Design: A multicentre retrospective comparative study was conducted in two hospitals in Lyon and one hospital in Saint-Etienne, France, between 1999 and 2022. Methods: In the SLA group, 46 patients were included and compared to 92 patients of the SA group. Demographic characteristics, medical history, clinical presentation, laboratory and imaging findings, treatments, and outcomes were collected and analysed from medical records. Results: The age at lymphoma diagnosis was significantly higher in the group in which sarcoidosis preceded lymphoma [65.9 years when sarcoidosis preceded lymphoma vs 48.3 years when both diseases occurred simultaneously vs 44.5 years when sarcoidosis followed lymphoma, p<0.001]. Hodgkin’s lymphoma was significantly more frequent in patients from group “simultaneous diseases" (p<0.001). There were significantly more autoimmune diseases (15.2% vs 2.17% p=0.007) in the SLA group, and patients with SA presented more frequently with night sweats (45.7% vs 11.6% p<0.001). Conclusions: No robust predictive factor of lymphoma development in patients with sarcoidosis was identified. However, it highlighted distinct clinical scenarios according to when lymphoma is diagnosed that must be taken into account by clinicians for disease management.